Toluene alkylation with methanol to p-xylene over heteropoly acids supported by clay - Bokade, Vijay V.; Deshpande, Suvarna S.; Patil, R.; Jain, S.; Yadav, G. D. (Journal of Natural Gas Chemistry, 2007)
{The alkylation of toluene with methanol for the selective formation of p-xylene was systematically studied. Very few studies have been reported on the use of superacids such as heteropolyacids on cheap supports, such as clay. This article deals with the use of different heteropoly acids (HPAs), viz, Dodeca-Tungstophosphoric acid [
Keywords: co-crystalline; p-xylene; toluene alkylation; ZSM-12; ZSM-5

Effect of rice husk particle size on ZSM-5 physico-chemical properties for selective formation of 1,3,5-trimethyl-2-benzylbenzene (Pharmaceutical Intermediate) - Ghuge, Gorakh; Niphadkar, Prashant; Rathod, Simmy; Bokade, Vijay V. (ChemistrySelect, 2021)
Rice husk, rich in silica and abundantly available as waste, is presently destroyed by burning, which creates environmental issues. Thus, it will be advantageous if this rice husk waste can be used for preparation of valuable products. One of the application is its use as silica source in the synthesis of zeolites like ZSM-5, which are silico-aluminates. Rice husk waste is available in wide range of particle sizes in agricultural farms. There is no study available in open literature on use of these wide particle ranges for its direct application. This paper is an attempt to use wide particle size rice husk, its effect on ZSM-5 synthesis and its physico-chemical properties. Further these prepared ZSM-5 catalyst was evaluated for benzylation of mesitylene reaction. The study found that, rice husk of 600 mu m particle size is optimum as far as ZSM-5 synthesis, its physicochemical properties and further its application in mesitylene benzylation reaction.
Keywords: Mesitylene; Particle size; rice husk; Silica Source; ZSM-5

Effect of CTMABr/SiO2 molar ratio in synthesis of micro-mesoporous ZSM-5 composite and its application in 5-EMF (biofuel additive) formation - Manal, Prajakta N.; Niphadkar, Prashant S.; Nandanwar, Sachin U.; Bokade, Vijay V. (Environmental Progress and Sustainable Energy, 2024)
Synthesis of micro-mesoporous zeolite composite with optimum micro and mesoporosity is an emerging research area due to its wide applications, especially in bulk chemical or biomass transformations. It offers advantages in preserving zeolite crystallinity, creating mesoporosity and converting bulky molecules into valuable products. This work presents the process of preparing bimodal micro-mesoporous ZSM-5 using dual templates (CTMABr and TPABr). XRD, N2 adsorption-desorption, SEM, TEM, Si-29, and Al-27 NMR were used to analyze the two-dimensional micro-mesoporous ZSM-5. One-step synthesis of bimodal micro-mesoporous ZSM-5 features dual micro/mesoporosity by a marginal decrease in the crystallinity (71%). Micro-mesoporous ZSM-5 composite was found to be dependent on the optimum CTMABr/SiO2 molar ratio of 0.04 to 0.06. The micro-mesoporous ZSM-5 zeolite composite was evaluated for cascade synthesis of 5-EMF (methoxymethyl furfural- biofuel additive) from fructose and exhibited a five fold increase in 5-EMF yield to 24.2% as compared with parent ZSM-5 (4.6%).
Keywords: fructose; methoxymethyl furfural-biofuel additive; micro-meso composite; ZSM-5